Is There a Cosmopolitan Information Seeker? - Becker, Helmut (Journal of International Business Studies, 1976)
This paper reports on some evidence from an international consumer survey in Germany and the United States which suggests the existence of an information-sensitive consumer-elite which transcends national boundaries. These Cosmopolitan Information Seekers, far higher in education, income, and social prestige than “average” consumers, represent a growing nucleus of “professional” consumers in the industrially advanced countries. The article also explores some of the implications which this segment has for the multinational corporation and the design of its marketing mix.